Effect of Hydrolysis Time and Sulfuric Acid Concentration on Reducing Sugar Content on Corn Cob Hydrolysis - Anisah Nur Jannah; Ahmad M Fuadi (CHEMICA: Jurnal Teknik Kimia, 2022)
Energy demand in Indonesia continues to increase, while the source of petroleum energy is a non-renewable energy source. This problem encourages people to seek alternative renewable and environmentally friendly fuels. Bioethanol is an alternative to replace petroleum energy that is environmentally friendly because it can be made from organic waste. The utilization of corncobs waste currently is not optimal. Corncobs are known to contain lignocellulose compounds, namely cellulose, hemicellulose, and lignin which are suitable as raw materials for making bioethanol. One of the conversions of lignocellulose into bioethanol is through hydrolysis. So in this study, the effect of hydrolysis time and sulfuric acid concentration (H2SO4) will be analyzed on the reducing sugar levels that will be produced because high reducing sugars will produce more bioethanol. The method of determining reducing sugar used is Nelson - Somogyi. The independent variables used were hydrolysis times that is 45 minutes, 90 minutes, 135 minutes, and 180 minutes, and the acid concentrations that are 5%, 10%, 15%, and 20% (1:20 w/v). The fixed variables used were corncob mass and hydrolysis volume, while the dependent variable was the reducing sugar content.